Identifying mechanic measures that best predict air-pistol shooting performance - Hawkins, R. (International Journal of Performance Analysis in Sport, 2011)
Key shooting mechanic measures were selected to identify how the measures were related to performance. Ten national-standard air-pistol shooters performed 60 simulated competition shots using their normal shooting procedures. An optoelectronic shooting system (NOPTEL ST 2000) was used to collect shooting mechanic measures and score. Multiple regression analysis results found the factors hold and aim to be important criterion. Hold and aim represented 48% of the total variance of the shooting score. The mechanic measure, Hitr (a measure of hold and smoothness of triggering which assesses the percent of time aiming in an area the size of the nine-ring when centred over the actual shot) was the most important individual criterion, representing 33% of the variance of the shooting score. Principal component analysis identified important measures and how they grouped among like measures. The results identified three factors which provide information on air-pistol shooting. First, hold described the ability to maintain the aiming point on the target. Second, time of hold described the amount of time the aiming point was on target. Third, aiming described accuracy of pointing the pistol onto the target. These measures reflect important information that should be used by the athlete during training.